RELATIONSHIP BETWEEN STUDENT LEARNING ENVIRONMENT, HOW TO LEARN AND LEARN MOTIVATION WITH RESULTS OF MATHEMATICS STUDENTS IN CLASS VIII SMP NEGERI 2 PLERET - Kurnia Prantauwati; Aris Thobirin (Universitas Ahmad Dahlan, 2017)
Based on the information from the students of SMP Negeri 2 Pleret Bantul District, students are less conducive to the learning environment, as well as learning styles about students’ learning motivation is low. This study aims to determine whether there is a positive and significant relationship between students’ learning environment, learning style and learning motivation the mathematics learning outcomes of class VIII SMP Negeri 2 Pleret Bantul District in the odd semester in the academic year of 2016/2017. The population of the research is all student's regular classes VIII of SMP Negeri 2 Pleret Bantul District of the odd semester in the academic year of 2016/2017 as many as 7 classes. Taken as a class VIII G class research sample by random sampling technique to class. Data collection techniques such as questionnaires and test engineering. Questionnaire research instrument for the variables of students’ learning environment, variable learning style, and variable learning motivation while research instrument outcome variables studied mathematics. Test using a research instrument validity, different power, and reliability testing. Analysis prerequisite test including normality test, independent test and linearity test. Data analysis for hypothesis testing using product-moment correlation analysis and multiple linear regression analysis. The results showed a positive and significant relationship between (1) the learning environment of students with mathematics learning outcomes, with R = 0.4317; (2) learning style with mathematics learning outcomes, with R = 0.5145; (3) learning motivation with mathematics learning outcomes, with R = 0.4012; (4) the learning environment of students and learning style with mathematics learning outcomes, with R = 0.5728; (5) students' learning environment and learning motivation with mathematics learning outcomes, with R = 0.4632; (6) learning style and learning motivation with mathematics learning outcomes, with R = 0.5725; (7) the learning environment of students, learning style and learning motivation with mathematics learning outcomes, with R = 0.5874 and the linear regression equation = -60,3895 + 0,2665 + 0,8747 + 0,5304 . Large donations are relatively = 21,7776%, = 58,7420% and = 19,4804% and the effective contribution = 7,5134%, = 20,2664% and = 6,7209%. This shows that the way of learning style (x2) have a greater relationship to mathematics learning outcomes.